Umbilical Cord Blood NOS1 as a Potential Biomarker of Neonatal Encephalopathy - Lei, Jun; Paules, Cristina; Nigrini, Elisabeth; Rosenzweig, Jason M.; Bahabry, Rudhab; Farzin, Azadeh; Yang, Samuel; Northington, Frances J.; Oros, Daniel; McKenney, Stephanie; Johnston, Michael V.; Graham, Ernest M.; et al. (Frontiers in Pediatrics, 2017)
BACKGROUND: There are no definitive markers to aid in diagnosis of neonatal encephalopathy (NE). The purpose of our study was: 1) to identify and evaluate the utility of neuronal nitric oxide synthase (NOS1) in umbilical cord blood as a NE biomarker; and 2) to identify the source of NOS1 in umbilical cord blood. METHODS: This was a nested case-control study of neonates >35 weeks gestation. ELISA for NOS1 in umbilical cord blood was performed. Sources of NOS1 in umbilical cord were investigated by immunohistochemistry, western blot, ELISA and quantitative PCR. Furthermore, umbilical cords of full term neonates were subjected to 1% hypoxia ex vivo. RESULTS: NOS1 was present in umbilical cord blood and increased in NE cases compared with controls. NOS1 was expressed in endothelial cells of the umbilical cord vein, but not in artery or blood cells. In ex vivo experiments, hypoxia was associated with increased levels of NOS1 in venous endothelial cells of the umbilical cord as well as in ex vivo culture medium. CONCLUSION: This is the first study to investigate an early marker of NE. NOS1 is elevated with hypoxia and further studies are needed to investigate it as a valuable tool for early diagnosis of neonatal brain injury.